2015
DOI: 10.1186/s12906-015-0776-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of treatment with Astragalus Membranaceus on function of rat leydig cells

Abstract: BackgroundAstragalus membranaceus (AM) is a Chinese traditional herb which has been reported to have broad positive effects on many diseases, including hepatitis, heart disease, diabetes and skin disease. AM can promote cell proliferation, increase the activities of superoxide dismutase (SOD) and glutathione peroxidase (GPx), and inhibit apoptosis by regulating the transcription of proto-oncogenes controlling cell death. While AM is included in some commercially available “testosterone boosting supplements”, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…The results of the current study were similar to previous studies on tilapia (Shi et al, 2013), swimming crab, Portunus trituberculatus (Meng, Liu, Li, Gao, & Chen, 2014), and puffer fish (Cheng et al, 2017). To date, many studies have confirmed that A. membranaceus and its extracts have significant antioxidant activities (Jia et al, 2012;X. L. Jiang et al, 2014;M.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results of the current study were similar to previous studies on tilapia (Shi et al, 2013), swimming crab, Portunus trituberculatus (Meng, Liu, Li, Gao, & Chen, 2014), and puffer fish (Cheng et al, 2017). To date, many studies have confirmed that A. membranaceus and its extracts have significant antioxidant activities (Jia et al, 2012;X. L. Jiang et al, 2014;M.…”
Section: Discussionsupporting
confidence: 90%
“…The results of the current study were similar to previous studies on tilapia (Shi et al, ), swimming crab, Portunus trituberculatus (Meng, Liu, Li, Gao, & Chen, ), and puffer fish (Cheng et al, ). To date, many studies have confirmed that A. membranaceus and its extracts have significant antioxidant activities (Jia et al, ; X. L. Jiang et al, ; M. Li et al, ). In this study, SOD, CAT, and GSH‐Px activities were significantly higher in the liver of AMEP‐supplemented groups than those in the NC group at 10°C, whereas the MDA content showed a reverse trend.…”
Section: Discussionmentioning
confidence: 96%
“…Astragaloside IV (AsIV) is one of the major active ingredients of the plant Astragalus membranaceus, which is referred to as HuangQi in Chinese. As an important Qi-invigorating medicinal herb, A. membranaceus is extensively used in traditional Chinese medicine for the treatment of cardiovascular diseases, hepatitis, and kidney and skin diseases (2,6,7). Chemically, AsIV is a cycloartane triterpene saponin with a well-defined molecular formula, the chemical structure of which is presented in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Ta-65 exerted a partial preservation of the normal structure of the seminiferous tubules and Leydig interstitial cells. In vitro treatment of cultured Leydig cells with Ta-65 increased the number of Leydig cells and elevated the production of testosterone in the culture media (Jiang et al, 2015). Pomegranate stimulates GnRH from hypothalamus to increase synthesis and secretion of LH and FSH from the anterior pituitary (Hong et al, 2008).…”
Section: Discussionmentioning
confidence: 97%